Mutagenesis of Thr-286 in monomeric Ca2+/calmodulin-dependent protein kinase II eliminates Ca2+/calmodulin-independent activity. - Waxham, M N (1990)
We have examined the role of Thr-286 autophosphorylation in the autoregulation of Ca2+/calmodulin-dependent protein kinase II. Using site-directed mutagenesis, we have substituted alanine or serine for Thr-286, or isoleucine for Arg-283, in the 50-kDa subunit of the kinase and expressed each protein in bacteria. Activation and autophosphorylation of all four enzymes were stringently dependent on Ca2+/calmodulin, indicating that neither Arg-283 nor Thr-286 is an absolute requirement for the pseudosubstrate inhibition of the enzyme. Autophosphorylation of the Ile-283 or Ala-286 enzyme generated little, if any, Ca2+/calmodulin-independent kinase activity, unlike the parent (Thr-286) or Ser-286 enzyme. The enzymes expressed in bacteria are predominantly monomeric, indicating that the generation of Ca2+/calmodulin-independent activity does not require the cooperative interactions of subunits normally present in the brain holoenzyme.